Master Gas System (MGS) – a Leap towards Zero Emission - Mahmoud A. Younis (Zenodo, 2022)
Abstract: Climate change has been the major occurring event worldwide and manifesting itself through record breaking events from strong hurricanes and floods, to wildfires in several worldwide countries, and melting glaciers in North Pole. In 2021, the United Nations issued a report that showed climate change is happening faster than predicted, and to reduce or control this change, global warming greenhouse gas (GHG) emissions must be reduced to net-zero. The two main sources of Greenhouse Effect are the increase in Carbon Dioxide and Methane gas in the atmosphere. Since 1970, Saudi Aramco was a pioneering oil and gas company to take extensive efforts to reduce carbon dioxide and methane gas in the atmosphere through a two-step approach: 1) reduction of carbon dioxide by switching to gas burning with full elimination of gas flaring into atmosphere, 2) “Net Zero” Greenhouse emission commitment by United Nations target date. To achieve these 2 goals, Gas plants and processing facilities were built where Saudi Aramco created its Master Gas System (MGS), the most ambitious engineering project undertaken by the company in the region. Due to the Kingdom’s increased energy demand, Saudi Aramco has continued to expand the MGS network (Phase I and II) reaching new customers in Central and Western regions. Recently, the Ministry of Energy and Saudi Aramco inaugurated the plans tostart a new Jafuragas plant which will increase gas production by 3 billion standard cubic feet of unconventional gas. To accommodate the additional gas, mega expansion of the existing Master Gas System (MGS) will be undertaken to deliver gas to new customers throughout the Kingdom including the south regions, Shoaiba and Shoqaiq. Keywords: Greenhouse Gases (GHG), Flaring, Emission, Net-Zero, Jafura. Title: Master Gas System (MGS) – a Leap towards Zero Emission Author: Mahmoud A. Younis International Journal of Engineering Research and Reviews ISSN 2348-697X (Online) Vol. 10, Issue 3, July 2022 - September 2022 Page No: 21-23 Research Publish ...